Standards and Certification of Marine Energy Conversion Systems (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The commercial success of emerging industries, such as marine energy, can be enhanced in the eyes of investors, insurers, regulatory authorities, end users, and public stakeholders by adherence to international standards, conformity assessment, and certification proctocols. Standards and certification are internationally-recognized methods the verify the safety and performance of renewable energy equipment and services.The exponential rise in the development of marine energy technologies now makes it one of the fastest growing clean energy-production industries. An abundance of marine energy technologies and designs are available to harness energy from clean, renewable resources. Marine energy technologies include Wave, Tidal, Ocean Current, River Current and Ocean Thermal Energy Converters.In 2007, the International Electrotechnical Commission (IEC) established Technical Committee (TC) 114,  “Marine energy – Wave, tidal and other water current converters”, to develop international standards for marine energy converter (MEC) technologies that provide electrical energy and other outputs such as desalinated seawater and heat exchange. Tidal barrage and dam hydraulic turbines are covered by IEC/TC 4. IEC standards are developed through consensus by subject matter experts who represent many countries and are then approved and published by globally recognized standards bodies including the IEC. Standards  comprise rules, guidelines, processes, or characteristics that allow users to repeatedly achieve the same outcome.In 2014, the IEC Renewable Energy System (IECRE) was established to develop conformity assessment protocols to achieve internationally-recognized certifications. The IECRE process for certification for any technology involves Verification and Validation. Verification is an assessment of a technology against a defined set of Standards or Codes through a design review. Validation is an assessment of a technology against the same set of Standards or Codes through testing. These activities are led by an IECRE accepted renewable energy certification body (RECB), often in conjunction with an IECRE accepted test laboratory. With regards to marine energy, the IECRE is responsible for developing and managing a framework where these technologies can be independently verified and validated.For example, following the IEC 62600-4 Technical Specification for Technology Qualification, an IECRE RECB with a scope for delivering technology qualification services, provides a gateway for these technologies to progress towards certification. This includes a robust assessment of the systems and subsystems of marine energy technologies, as well as the quality of integration between them and external sytems they are expected to interface with.IEC TC 114 and IECRE provide liaison with IEA-OES to collaborate on policy and development, as evidenced by the issue of the IEA-OES, IEC TC 114 and IECRE joint publication “Supporting Ocean Energy Technology Development and Commercialization: Coherent Application of Guidance, Standards and Certification”.This presentation will discuss progress to date in IEC international standards for marine energy and IECRE conformity assessment and certification. As of January 2025, IEC/TC 114 has 205 Subject Matter Experts representing 18 participating member countries and 12 observer member countries and 15 consensus-based Technical Specifications. TC 114 is evolving the title and scope of work from a focus on marine energy converters to marine energy conversion systems.